Atividade repelente e carrapaticida de extratos e óleos essenciais de plantas sobre o carrapato bovino Rhipicephalus microplus - LIMA, Aldilene da Silva (2014)
Rhipicephalus microplus is an ectoparasite of major economic importance to cattle. The control cattle tick has difficult by resistance of populations to synthetic acaricides. Plant bioactive molecules can be an alternative to control this ectoparasite. The aim of this study was to evaluate the repellent and acaricide effect of extracts and essential oils from plants on the cattle tick R. microplus. Hexane, ethyl ether, ethanolic, and methanolic extracts was obtained of P. tuberculatum fruits. After extraction, all of the extracts were dried. Essential oil from L. alba was obtained by hydrodistillation, all oil essential of Citrus ssp. were extracted by cold pressing fruits and all the identification of the major compounds of essential oils was performed by gas chromatography coupled to mass spectrometry (GC-MS) and gas chromatography flame ionization detector (GC-FID). Monoterpenes was obtained commercially. All the extracts was use larval packet tests and Adult immersion tests. Oil essential was used to repellency test. All extracts showed highest larvicidal activity against R. microplus. Hexane extract showed a CL50 of 0.04 mg/mL, CL50 ethyl ether of 0.08 mg/mL and ethanolic LC50 of 2.73 mg/mL. P. tuberculatum fruit extracts were also effective against engorged females R. microplus. Genotypes LA-13 and LA-57 of L. alba showed repellent activity against larvae of R. microplus more than 40 hours at concentration of 6.88 mg/cm². Monoterpenes showed lower repellent activity. Oil essenctial of Citrus aurantium var. dulcis showed repellent activity more than 30 hours at concentration of 6.88 mg/cm². Other essential oils tested showed a time of repellency lower 5 hours. Ours results reported than plants contains bioactive compounds with great potential acaricides, and they can be commercial products for the control of R. microplus.